Performance Efficiency of Higher Education in Indonesia: a Stakeholders’ Perspective - Wardoyo, Cipto; Herdiani, Aulia; ., Sulastri; ., Sulikah (International Journal of Engineering and Technology, 2018)
This study aims at analyzing the necessity of performance evaluation in higher education institutions based on a benchmarking model of Educational Development Efficiency (EDE), which further will be employed to analyze the inclination of stakeholder in deciding which program and university they prefer to choose. The analysis is performed by using binary logistic regression to predict the inclination of stakeholder based on provided assessment factors. The results of this study are consistent with previous studies where input variables in EDE model significantly influence the quality of university outcomes. Furthermore, referring to observed factors, quality of academic services and comprehensive quality of educational institution are emphasized by a stakeholder in choosing program and university, while the rank issued by National Accreditation Institution of Higher Education in Indonesia contributes as supporting information.Â Â